2021
DOI: 10.1186/s13613-021-00828-2
|View full text |Cite
|
Sign up to set email alerts
|

Continuous positive airway pressure for respiratory support during COVID-19 pandemic: a frugal approach from bench to bedside

Abstract: Background We describe a frugal approach (focusing on needs, performance, and costs) to manage a massive influx of COVID-19 patients with acute hypoxemic respiratory failure (AHRF) using the Boussignac valve protected by a filter (“Filter Frugal CPAP”, FF-CPAP) in and out the ICU. Methods (1) A bench study measured the impact of two filters with different mechanical properties on CPAP performances, and pressures were also measured in patients. (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 32 publications
0
20
0
2
Order By: Relevance
“…Search terms yielded 84 articles relating to a total of 13 140 patients after exclusion of duplicates, and after screening titles, abstracts, and full text for relevance specifically to outcomes with the use of NIRS in patients with COVID-19 ( appendix p 1 ). 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Studies Of Nirs In Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Search terms yielded 84 articles relating to a total of 13 140 patients after exclusion of duplicates, and after screening titles, abstracts, and full text for relevance specifically to outcomes with the use of NIRS in patients with COVID-19 ( appendix p 1 ). 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Studies Of Nirs In Covid-19mentioning
confidence: 99%
“…Other than two multicentre RCTs from Italy and the UK, 38 , 95 22 prospective and 61 retrospective observational studies were identified, reporting a median of 71 patients (IQR 40–127) per study. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ,…”
Section: Studies Of Nirs In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Xtype mixer appropriately performs in the terms of oxygen homogeneity, but it greatly increases hydraulic resistance (+15%). Similar questions have also been raised in literature adding a viral/bacterial lter proximally to patient [10]. To deal with this problem, a custom mixer has been designed that allowed mixing oxygen with homogeneity >99.5% and low hydraulic resistance (+5%).…”
Section: Ventilator Descriptionmentioning
confidence: 90%
“…During the COVID-19 pandemic, P-SILI has been much debated, especially when balancing the risk of early versus late intubation [ 17 , 18 ]. Assessment of such risk has generally been biased by the need to use noninvasive strategies in exceptional settings of massive influx of patients and concomitant shortage of ICU beds and mechanical ventilators [ 75 , 76 , 77 , 78 , 79 ]. Anyway, there is no strong evidence from observational studies that timing of intubation have altered the outcome [ 80 , 81 , 82 ], letting wide open the area of research.…”
Section: Usefulness Of the Concept Of P-sili In Clinical Practicementioning
confidence: 99%